2022
DOI: 10.1155/2022/5670303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Mechanical Traction as Physical Therapy for Lumbar Disc Herniation: A Meta-Analysis

Abstract: Objective. This study is aimed at exploring the clinical effect of mechanical traction on lumbar disc herniation (LDH). Methods. Related literatures were retrieved from PubMed, Medline, Embase, CENTRAL, and CNKI databases. Inclusion of literature topic was comparison of mechanical traction and conventional physical therapy for lumbar disc herniation. Jadad scale was used to evaluate the quality of the included RCT studies. The Chi-square test was used for the heterogeneity test, and a random effect model was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A recent metaanalysis suggested that in individuals with herniated discs, mechanical traction can effectively alleviate lumbar and leg pain, but has no noticeable impact on spinal motion. Additionally, it reported that mechanical traction has a therapeutic impact that is noticeably superior to that of traditional physical therapy [13], whereas William's flexion exercises involving a series of components are also effective in reducing pain and disability as given in a narrative review by Kim et al [9]. Both interventions combined with DT boosted the intervention protocol described in this case report.…”
Section: Discussionmentioning
confidence: 64%
“…A recent metaanalysis suggested that in individuals with herniated discs, mechanical traction can effectively alleviate lumbar and leg pain, but has no noticeable impact on spinal motion. Additionally, it reported that mechanical traction has a therapeutic impact that is noticeably superior to that of traditional physical therapy [13], whereas William's flexion exercises involving a series of components are also effective in reducing pain and disability as given in a narrative review by Kim et al [9]. Both interventions combined with DT boosted the intervention protocol described in this case report.…”
Section: Discussionmentioning
confidence: 64%
“…The incidence of sciatica is between 13% and 40%, and the most prevalent cause of sciatica in adults is lumbar disc herniation (LDH) [ 1 ]. LDH is prevalent among adults aged 25 to 55 years who spend a considerable proportion of their time sitting or standing with heavy workloads [ 2 ]. LDH is an orthopedic condition characterized by the displacement of an intervertebral disc from its anatomical position, usually caused by trauma or degenerative changes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…LDH is prevalent among adults aged 25 to 55 years who spend a considerable proportion of their time sitting or standing with heavy workloads [ 2 ]. LDH is an orthopedic condition characterized by the displacement of an intervertebral disc from its anatomical position, usually caused by trauma or degenerative changes [ 2 ]. This displacement can occur as a result of a traumatic injury or degenerative changes due to the aging process [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment modalities such as super cial and deep heaters, massage, electrotherapy, and traction are used in the physical therapy of low back pain (3). It has been determined that these treatments are effective in reducing pain and improving function in patients with lumbar disc herniation.…”
Section: Introductionmentioning
confidence: 99%